Development of roGFP2-derived redox probes for measurement of the glutathione redox potential in the cytosol of severely glutathione-deficient rml1 seedlings - Aller, Isabel; Rouhier, Nicolas; Meyer, Andreas J. (Frontiers in Plant Science, 2013)
Glutathione is important for detoxification, as a cofactor in biochemical reactions and as a thiol-redox buffer. The cytosolic glutathione buffer is normally highly reduced with glutathione redox potentials (EGSH) of more negative than -310 mV. Maintenance of such negative redox potential is achieved through continuous reduction of glutathione disulfide by glutathione reductase. Deviations from steady state glutathione redox homeostasis have been discussed as a possible mean to alter the activity of redox-sensitive proteins through switching of critical thiol residues. To better understand such signalling mechanisms it is essential to be able to measure EGSH over a wide range from highly negative redox potentials down to potentials found in mutants that show already severe phenotypes. With the advent of redox-sensitive GFPs (roGFPs), understanding the in vivo dynamics of the thiol-based redox buffer system became within reach. The original roGFP versions, roGFP1 and roGFP2, however, have midpoint potentials between -280 and -290 mV rendering them fully oxidized in the ER and almost fully reduced in the cytosol, plastids, mitochondria and peroxisomes. To extend the range of suitable probes we have engineered a roGFP2 derivative, roGFP2-iL, with a midpoint potential of about -238 mV. This value is within the range of redox potentials reported for homologous roGFP1-iX probes, albeit with different excitation properties. To allow rapid and specific equilibration with the glutathione pool, fusion constructs with human glutaredoxin 1 (GRX1) were generated and characterized in vitro. GRX1-roGFP2-iL proved to be suitable for in vivo redox potential measurements and extends the range of EGSH values that can be measured in vivo with roGFP2-based probes from about -320 mV for GRX1-roGFRP2 down to about -210 mV for GRX1-roGFP2-iL. Using both probes in the cytosol of severely glutathione-deficient rml1 seedlings revealed an EGSH of about -260 mV in this mutant.